2022
DOI: 10.2196/34966
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Preventive Behaviors and Health Literacy, Information Evaluation, and Decision-making Skills in Japanese Adults: Cross-sectional Survey Study

Abstract: Background Health literacy is important for the prevention of COVID-19 transmission. Research in Japan shows that health literacy is related to skills in evaluating information and decision-making (skills that are not necessarily limited to information about health). Such basic skills are important, particularly when individuals encounter new health issues for which there is insufficient evidence. Objective We aimed to determine the extent to which COVI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 32 publications
(43 reference statements)
4
8
0
Order By: Relevance
“…Workers who have received COVID-19 infection prevention education will have a higher level of knowledge about COVID-19. It is consistent with the results of previous studies [ 35 , 38 , 39 ], which state that the higher the level of knowledge, the higher the performance of infection prevention actions. Therefore, it is necessary to provide consistent health information education in order to increase access to health information at work.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Workers who have received COVID-19 infection prevention education will have a higher level of knowledge about COVID-19. It is consistent with the results of previous studies [ 35 , 38 , 39 ], which state that the higher the level of knowledge, the higher the performance of infection prevention actions. Therefore, it is necessary to provide consistent health information education in order to increase access to health information at work.…”
Section: Discussionsupporting
confidence: 92%
“…A study conducted in Sydney on adults reported that people with low health literacy had a higher risk of infection and mortality because they were less capable of understanding the symptoms of COVID-19 and identifying infection prevention behaviors [ 34 ]. Moreover, another study on Japanese adults also reported that health literacy influenced COVID-19 infection prevention behaviors [ 35 ]. Consequently, differences in health literacy between individuals can lead to the transmission of COVID-19 to others, and thus, enhancing health literacy in individuals for the prevention of COVID-19 is an important part of healthcare for the worker groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study conducted in the region of Tuscany, in Central Italy, general HL was found to be a predictor of both better self-reported knowledge and an attentive attitude toward the importance of COVID-19 preventive measures, whereas it had no role in predicting a higher risk perception [ 15 ]. Similar results have also been observed in a Japanese survey [ 27 ]. In the present study, high levels of HL-COVID are associated with excellent HL-VAC, especially in the subdimensions ‘find’, ‘understand’, and ‘prevent’.…”
Section: Discussionsupporting
confidence: 91%
“…People with higher level of HL were more likely to form healthy lifestyles and adopt preventive measures. Many studies on the relationship between HL and health behaviors have supported the protective effects of HL (20,(43)(44)(45)(46), prompting us to consider improving HL as a critical measure to curb the pandemic (47). Better understanding, appreciation, and application of health information can support actions at multilevel to address major public health challenges (48).…”
Section: Discussionmentioning
confidence: 99%